Patients' Complaints and the Effective Factors in Medical and Educational Center of Shahid Bahonar Hospital of Kerman in 2015 - Mohammad Ranjbar; Mehdi Ahmadinejad; Shiva Sheikholeslami (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Patients’ complaints show dissatisfaction from the services received in hospital and gaps in health care service providing system. The present research was conducted with the aim of determining patients’ complaints and the effective factors in Shahid Bahonar Hospital of Kerman in 2015. Methods: This research is cross-sectional with descriptive-analytical approach and studied all the recorded complaints in Shahid Bahonar Hospital of Kerman in 2015. Data was collected using form as census from 155 recorded complaints from office of complaints in accountability unit in 2015. Data was analyzed after extraction by SPSS22 software, descriptive statistics, and chi-square test.   Results: Complaints of 155 people with 174 subjects were recorded. The maximum complaints were for clinical sector (54.2%). Each non-receiving desirable services and improper communication was the most proposed subject. Frequency of complaints based on team and doctors was 31.6% and administrative-support team was 30.5% as the maximum frequency. The most popular complaint subject for men was non-receiving timely, conscious, and desirable services with 23.87% frequency, and for women was improper communication and confrontation with 17.41% frequency. The efficient evidences based on relationship between genders and age weren’t found among subjects. conclusion: One hundred and fifty five complaints were recorded in Shahid Bahonar Hospital of Kerman in 2015. The reason for patients’ complaints was non-receiving desirable services, improper communication, defect in facilities and amenities, ignorance to cares and costs. The most frequent factor was non-receiving timely, conscious, and desirable services. Therefore, it is suggested that senior managers of this center should formulate a proper operational program to promote medical services. Moreover, a permanent follow up of mangers to increase number of approved beds and facilities for patient admission and treatment will reduce the amount of complaints.